(untitled) (Linguostylistic Studies, 2015)
The paper deals with the role of modern Ukrainian press in extending the lexical system with compound words. Their derivative types are also described here. Press as a representative of modern Ukrainian literary language simultaneously performs various functions, such as: it shows lexical and derivative changes in the language, and represents functional and stylistic standards of writing communication, and influences modern common tendencies. The author argues that the mass-media and the press in particular is a factor enriching and renewal Ukrainian vocabulary, formation of linguistic norms. Mass-media language and Ukrainian language itself is actively added with compound words under external and internal linguistic factors. Common used composite, juxtapositional and abbreviated words compose the language base of the press. Neologisms and occasional compound derivatives, hybrid elements, compound words with positive or negative meaning distinguish on their background. Key words: the press, a compound word, composite, juxtapositional, abbreviated word. References